Research Updates on Type 2 Diabetes in Children. (May 2013) - Linder, Barbara; Imperatore, Giuseppina
Major research trials have provided insight into the scope of type 2 diabetes in youth. The National Diabetes Education Program offers resources to help school nurses support children with or at risk for type 2 diabetes.